Improvement of signal synchronization in GPS software receiver - Sokolović, Vlada S.; Marković, Goran B.; Dikić, Goran D. (Vojnotehnički glasnik / Military Technical Courier, 2015)
In GPS receivers, navigation bit allocation is performed throughout the process of signal tracking and detection. In the process of signal tracking, the locally generated signal must be synchronized with the received signal. The Costas phase-locked loop (PLL) behavior, which is often used for signal synchronization, is characterized by dominant tracking error sources. The resulting phase tracking errors are significant in the presence of weak signals, i.e. signals with the low signal-to-noise ratio (SNR). In order to improve the signal synchronization and enable signal tracking by the receiver, we here proposed the usage of a non-data-aided (NDA) phase estimator. Based on the practical processing of the GPS signals, it is shown that the applied NDA algorithm is more resistant to sudden changes in frequency (phase) of the input signal than the previously considered phase discriminator in the Costas PLL. Also, we have shown that the solution analyzed here exhibits more stable operation in signal tracking for a low SNR.
Keywords: global positioning system; phase estimation; receiver; signal processing; software